Effects of garlic tablet (GARLET) in combination with telmisartan on high blood pressure - Rahimi Ahmad Mustafa; Ayami, Haseebullah; Halimi, Mahbubullah (Published by Universitas Gadjah Mada, 2024)
Hypertension (HTN) is a health problem worldwide affecting tens of millions of people. Giving modern antihypertensive alone is not enough to cure this disease. Garlic has been used to treat and cure various diseases, including high blood pressure (BP). This study aims to evaluate the effectiveness of administering telmisartan with garlic in reducing BP. In this study, 96 people with mild to moderate HTN were randomly selected and assigned to three groups consisting of 32 subjects; each participant in the garlic group received 400mg BD, the telmisartan group received 20mg OD, and the mixed group received 400 mg garlic BD and 20mg telmisartan OD for 8 wk of treatment. Blood pressure was measured at the beginning of each week, as well as on the closing day of the 8 wk. Combining telmisartan with garlic is more effective in reducing systolic blood pressure/SBP (113.0±22.9 mmHg) compared to telmisartan (147.7±4.6 mmHg; p=0.015) and diastolic blood pressure/DBP (71.0±21.2 mmHg vs 90.75±11.9 mmHg; p=0.038) during 8 wk of treatment in hypertensive patients. No significant side effects were identified during the treatment period. In conclusion, garlic, like other BP control pills, increases the effectiveness of chemical pills to lower SBP and DBP.